Reviving the 'double jeopardy' hypothesis: Physical health inequalities, ethnicity and severe mental illness. (September 2016) - Das-Munshi, Jayati; Stewart, Robert; Morgan, Craig; Nazroo, James; Thornicroft, Graham; Prince, Martin
Summary: People with severe mental illness (SMI) experience a reduction in life expectancy of 15–20 years. Physical health and mortality experience may be even worse for ethnic minority groups with SMI, but evidence is limited. We suggest clinical, policy and research recommendations to address this inequality.